In-vitro Screening of Antibacterial Activities of Selected Wild Tuberous Plants of Odisha, India - Swain, Jugajyoti; Kumar, Sanjeet; Parida, Sagarika; Jena, Padan Kumar (Asian Journal of Biological and Life Sciences, 2020)
Tuberous plants are the resources of many useful bioactive compounds. It suggests that they may probably protect the humans against microbial pathogens. Keeping this in view, an attempt has been made to analyze the microbial potentials. Eight species of tuberous plants (Dioscorea belophylla, D. esculenta, D. glabra, D. oppositifolia, D. tomentosa, D. wallichii, D. hamiltonii and D. hispida var. daemona) were collected from peripheral areas of Similipal Biosphere Reserve, Mayurbhanj, Khordha, Cuttack and Puri districts of Odisha. Methanol, acetone and aqueous extracts were extracted and bioactive compounds were detected. In all the extracts of the above selected plants, phenolic compounds, tannin and saponin were detected as the chief bioactive compounds. Antibacterial activities were carried out using agar well diffusion and disc diffusion assay against selected bacterial pathogens,Streptococcus mutans(MTCC 497),Streptococcus pyogenes(MTCC 1926),Vibrio cholerae(MTCC 3906),Shigella flexneri(MTCC 1457) andSalmonella typhi(MTCC 1252). The minimum inhibitory concentration (MIC) values were determined using broth dilution assay. Results revealed that all the extracts showed significant antibacterial activity using the said methods. Methanol extract of all experimental plants showed highest activity against MTCC 1926 and MTCC 497. Present investigation highlights the antibacterial potential of tuberous plants available in Odisha state.
Keywords: Agar well diffusion; Antibacterial activities; Bioactive compounds; Disc diffusion assay; Tuberous plants.